Ungulate browsing blocks restoration of coniferous European Sand Belt forests into a broadleaved state - den Ouden, Jan; Jansen, Patrick A.; Krul, Leontien; Visser-Winterink, Annemieke; Leidekker, Jakob (Elsevier BV, 2026)
Tree browsing by ungulates may act as a strong biotic filter on forest regeneration. In the western part of the so-called European sand belt, browsing is believed to block restoration of coniferous forests into a broadleaved-dominated state, but this process remains poorly documented. The aim of this study was to better understand the dynamics of tree recruitment in a forest landscape at the European sand belt, using food selection and apparent competition via shared natural enemies as frameworks. We monitored tree regeneration and browsing during 2012–2024 in permanent plots across De Hoge Veluwe National Park (the Netherlands) in transects as well as in exclosures paired with control plots. We found that food selection was not mediated by landscape-level characteristics, but rather by tree species identity. Tree species preferred by ungulates had less height growth when subject to browsing. Exclusion of ungulates led to a substantial increase in height growth of preferred species, while the relative height of avoided species was reduced, indicating apparent competition. Forest regeneration inside exclosures converged to a community of mixed broad-leaved species. These results confirm that browsing in this system indeed hampers the restoration of coniferous forest towards a broadleaved forest. Attempts to diversify these forests and increase resilience to climate change cannot succeed under current ungulate densities.
Keywords: Apparent competition; Capreolus capreolus; Cervus elaphus; De Hoge Veluwe National Park; Forest restoration; Temperate forest; Tree regeneration; Forestry; Nature and Landscape Conservation; Management, Monitoring, Policy and Law; SDG 13 - Climate Action